Self-Regulation as a Protective Factor Against Work Stress in Special Education Teachers - Miatari, Exwati; Setyorini, Theresia Dewi; Rizqia, Ayu Gigih (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Inclusive education is a service provided to students with special needs in regular schools, including those who experience learning difficulties. During the learning process, these students are accompanied by special education teachers who possess the necessary qualifications to fulfill this role. The demands and pressures of the job can potentially lead to work stress, making self-regulation skills essential for teachers to perform their duties effectively. This study aims to examine the relationship between self-regulation and work stress among special education teachers. The study involved 70 teachers in the Special Region of Yogyakarta, selected using a convenience sampling technique. Data were collected using self-regulation and work stress scales developed by the researchers. Data analysis was conducted using Pearson’s product-moment correlation with the aid of SPSS version 24.0 for Windows. The results showed a highly significant negative correlation between self-regulation and work stress (r = -0.548; p = 0.001), with an effective contribution of 41.55%. Further analysis of the components of self-regulation revealed that self-reactive influences contributed the most (18%), followed by self-monitoring (15.2%) and the judgemental subfunction (8.4%). These findings indicate that self-regulation plays an important role in reducing work stress among special education teachers.Pendidikan inklusi merupakan layanan bagi peserta didik berkebutuhan khusus di sekolah reguler, termasuk mereka yang mengalami hambatan belajar. Dalam proses pembelajaran, peserta didik tersebut didampingi oleh guru pembimbing khusus yang telah memiliki kualifikasi pendidikan untuk menjalankan peran tersebut. Tuntutan dan tekanan dalam pekerjaan berpotensi menimbulkan stres kerja, sehingga diperlukan kemampuan regulasi diri yang baik agar guru dapat menjalankan tugas secara optimal. Penelitian ini bertujuan untuk mengetahui hubungan antara regulasi diri dan stres kerja pada guru pembimbing khusus. Subjek penelitian berjumlah 70 orang guru di Daerah Istimewa Yogyakarta yang dipilih menggunakan teknik convenience sampling. Pengumpulan data dilakukan dengan menggunakan skala regulasi diri dan skala stres kerja yang disusun oleh peneliti. Analisis data menggunakan korelasi product moment dengan bantuan program SPSS versi 24.0 for Windows. Hasil analisis menunjukkan terdapat hubungan negatif yang sangat signifikan antara regulasi diri dan stres kerja (r = -0,548; p = 0,001), dengan sumbangan efektif sebesar 41,55%. Uji lanjutan terhadap aspek regulasi diri menunjukkan bahwa self-reactive influences memberikan kontribusi paling besar (18%), diikuti oleh self-monitoring (15,2%) dan judgemental subfunction (8,4%). Temuan ini menunjukkan bahwa regulasi diri berperan penting dalam menurunkan tingkat stres kerja pada guru pembimbing khusus.